CHANGES IN OVARIAN DEVELOPMENT AND SERUM LEVELS OF VITELLOGENIN UNDER DIFFERENT ACCLIMATION TO TEMPERATURE IN CHELA CLUPEOIDES (BLOCH, 1795 - DASH, PRAGYAN; K. D. RAWAT; KASHYAP , DIPANJAN; A. P. SHETE (The Bioscan, 2013)
An experiment to assess the effect of temperature on ovarian development and serum levels of vitellogenin in Chela clupeiodes was conducted at aquaculture division of Central Institute of Fisheries Education (CIFE), Mumbai for a period of 60 days from the month of January to February. Results showed that raising temperature to 30°C significantly enhanced GSI (6.11±0.55 – 14.7±0.42) but beyond that temperature the GSI increment was less (3.5±0.4 - 6.4±0.41). Histological examination revealed better maturity with higher percentage of mature oocytes (24.753±1.366) in treatment T3 (30°C). Elevated temperature exposure beyond 30°C showed poor maturation with lower percentage of mature oocytes (3.486±0.633). Estimation of serum vitellogenin level showed elevated temperature above 30°C resulted in reduction of their capacity to be sequestered into growing oocytes. After 60 days of rearing serum level of vitellogenin attained its peak at treatment T3 (30°C). By the present investigation it can be concluded that elevated temperature may increase ovarian maturation in Chela clupeiodes but up to a certain threshold limit beyond that it has a negative impact on gonadal development and vitellogenin level in serum.